Practical applications of data processing, algorithms, and modeling - Whig, Pawan 1980-; Sharma, Sachin; Sharma, Seema; Jain, Anupriya 1977-; Yathiraju, Nikhitha 1994- (IGI Global, 2024)
The book serves as a practical guide, providing hands-on examples, case studies, and problem-solving scenarios. It aims to empower readers to confidently navigate through data challenges and make informed decisions using data-driven insights.
Keywords: Big data; Computer simulation; Engineering -- Data processing